Modal Sosial Workshop pada Kedai Kopi Bersaudara di Kota Mojokerto - Faizal Bahrul Ilmi (Paradigma, 2024)
Coffee shop ”Bersaudara” is a coffee shop that conducts various innovations to continue growing to be better and more competitive. One of the innovations currently being developed is routine activities in the form of mini workshop. The aim of this research was to analyze the social capital of workshop at coffee shop ”Bersaudara” in Mojokerto City. This research uses social capital theory from Pierre Bourdieu. Social capital forms a network of resource in determining and reproducing social position. The capital owner in this research is the owner of coffee shop ”Bersaudara”. The approach used by researcher to conduct this research is a qualitative approach. The result of the research states that there have been many strategies carried out by capital owner to maintain their power, one of which is workshop activities. The social capital created by capital owner in the form of workshop at coffee shop ”Bersaudara” provides many benefits. One of them is to support the continuity of capital owner. The capital owner in coffee shop ”Bersaudara” is the owner of coffee shop ”Bersaudara”. The owner of the Coffee shop ”Bersaudara” consists of 3 people, namely Achnu Arifudin, Firmansyah Sasmita, and Muhammad Tajuddin Zain. The three capital owners are fully responsible for the development and progress of coffee shop ”Bersaudara”. The three capital owners must also maintain their power by advancing the coffee shop ”Bersaudara”. The three capital owners of coffee shop ”Bersaudara” have balanced and impartial contribution. Keywords: coffee shop, social capital, capital owner, workshop